PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON MENGENALI SIKLUS PADA MAKHLUK HIDUP UNTUK MENINGKATKAN MOTIVASI BELAJAR MURID KELAS III DI SD NEGERI TEGALREJO II - Ni’mah Fatahanisa; Arip Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an animated video learning media based on Powtoon on the topic of recognizing the life cycle of living things to improve the motivation and learning outcomes of third-grade elementary school students. This research used the Research and Development (R&D) method with the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The study was conducted at SD Negeri Tegalrejo II involving 54 third-grade students from classes III A and III B. Data collection techniques included expert validation questionnaires (material and media experts), teacher and student response questionnaires, and learning outcome tests in the form of pretest and posttest. The data were analyzed using descriptive quantitative analysis to determine the feasibility, practicality, and effectiveness of the developed media. The results showed that the Powtoon-based learning media developed was categorized as very feasible, with an average feasibility percentage of 85% based on the assessments of material and media experts. The practicality test also indicated very positive responses from teachers and students, with a convenience percentage of 87.5% and practicality of 100%. Furthermore, the implementation results demonstrated an improvement in students’ learning outcomes, as indicated by the increase in the average scores of pretest and posttest in both limited and field trials. The results of the paired sample t-test showed a significance value of 0.000 (<0.05), indicating a significant difference before and after the use of the media. Therefore, the Powtoon-based learning media is considered valid, practical, and effective for use in IPAS learning on the life cycle of living things in elementary schools.